Worlds apart : why poverty persists in rural America - Duncan, Cynthia M. (Yale University Press, 1999)
The author "examines the nature of poverty in Blackwell in Appalachia and in the Mississippi Delta town of Dahlia" and contrasts them to New England's Gray Mountain's "rich civic culture that enables the poor to escape poverty."--Jacket